2021
DOI: 10.3390/microorganisms9010109
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibitory Effect of Endophyte-Infected Tall Fescue on White Clover Can Be Alleviated by Glomus mosseae Instead of Rhizobia

Abstract: In artificial ecosystems, mixed planting of gramineous and leguminous plants can have obvious advantages and is very common. Due to their improved growth performances and stress tolerance, endophyte-infected grasses are considered to be ideal plant species for grasslands. However, endophytic fungi can inhibit the growth of neighboring nonhost leguminous plants. In this study, we chose endophyte-infected and endophyte-free tall fescue (Lolium arundinaceum Darbyshire ex. Schreb.) and clover (Trifolium repens) as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 79 publications
(91 reference statements)
0
5
0
Order By: Relevance
“…For example, sweet clover contains coumarin [71] and aromatic phenolic compounds, which (when excreted by plant roots) may affect both N-fixers [72] and the other rhizobacteria. Some of these root microorganisms may counter-act as allelopathic elements [73,74] and chemically modulate final plant response to pH, osmotic potential, or complete soil microbial community [75,76].…”
Section: Microbial Soil Propertied In Rhizosoil and Bulk Soil And The...mentioning
confidence: 99%
“…For example, sweet clover contains coumarin [71] and aromatic phenolic compounds, which (when excreted by plant roots) may affect both N-fixers [72] and the other rhizobacteria. Some of these root microorganisms may counter-act as allelopathic elements [73,74] and chemically modulate final plant response to pH, osmotic potential, or complete soil microbial community [75,76].…”
Section: Microbial Soil Propertied In Rhizosoil and Bulk Soil And The...mentioning
confidence: 99%
“…Regarding the effect of endophyte infection on rhizobia in the host habitat, only the effect of cultivated grass, such as tall fescue and perennial ryegrass, on nodule number has been reported. In a mixed system of tall fescue with white clover and perennial ryegrass with white clover, endophyte infection significantly reduced the nodulation number of legume plants (García Parisi et al 2015;Liu et al 2021). In native grasslands, the diversity of both endophytes and rhizobia is higher than that of cultivated grassland.…”
Section: Discussionmentioning
confidence: 96%
“…Can endophyte infection further affect the growth of legumes by affecting nodule formation? Studies using E+ tall fescue in mixture with alfalfa, red clover (Staley and Belesky 2004) and white clover (Liu et al 2021) have found that endophyte infection reduces the number of legume root nodules as well as the growth of legume plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Arti cial grasslands have been identi ed as a potent approach for boosting grass production and quality, emerging as a noteworthy source of high-quality forage grasses (Chen et al 2021). In comparison to monoculture grassland, mixed grassland planting offered the bene ts of high grass yield and superior quality (Liu et al 2021; Tahir et al 2022), while also enhancing soil quality, and fertility (Liu et al 2023; Coêlho et al 2019), and resource utilization e ciency (Liu et al 2022b). Furthermore, Li (Li et al 2009) stated that mixing leguminous and gramineous plants in intensive farming systems signi cantly reduced the inhibitory effects of nitrogen fertilization on nodulation and nitrogen xation.…”
Section: Introductionmentioning
confidence: 99%